Transformasi Digital Perbankan: Analisis Minat dan Persepsi Gen X Terhadap Penggunaan Mobile Banking di Era Cashless Society - Putri Nurhayati; Nurwani Nurwani; Kusmilawaty Kusmilawaty (Politeknik Ganesha Medan, 2026)
This study aims to understand Generation X's interests and perceptions of mobile banking in the cashless society era. The method used was descriptive qualitative, involving 10 informants aged 45–60 years in Medan who are mobile banking users. Data were collected through in-depth interviews and then analyzed using thematic analysis, encompassing data reduction, data presentation, and conclusion drawing. The analysis results indicate that informants' interest in continuing to use mobile banking is high. This interest is driven not only by technical convenience, but also by repeated positive experiences, a sense of security in the system, and a desire to try new features. Support for security features such as OTP, biometric verification, and PIN further strengthens their level of trust in the application. The perception analysis results indicate that most informants experienced doubt and confusion at the beginning of use. However, as usage increased, these perceptions changed to become more positive. The simple interface, assistance from family members (especially children who are more tech-savvy), and successful transactions convinced them that the application was easy to use (perceived ease of use) and useful (perceived usefulness).